Regulation of the Right to Strike for Professional Sportsmen in Indonesian and Spanish Law Perspectives - I Made Artha Rimbawa; I Ketut Satria Wiradharma Sumertajaya; Putu Eka Trisna Dewi; I Kadek Alit Ambara Wijaya (Journal Equity of Law and Governance, 2024)
Strikes are a fundamental right of workers across the globe, representing a manifestation of the right to freedom of association and the protection of the right to organise. It thus falls upon the state to safeguard the right to strike, which may be achieved, for instance, by enacting national legislation that strikes a fair balance between the interests of professional sportsmen and those of their employers. In light of the above, the present study focuses on the examination of the regulation of the right to strike for professional sportsmen in the context of Indonesian and Spanish laws. In this research, the author employs a normative legal research method with a statute approach and a comparative approach. The findings of this research demonstrate that the regulation of the right to strike for professional sportsmen in Indonesian and Spanish law exhibits notable differences. The right to strike is specifically regulated in Spain by the Ley 39/2022, De 30 De Dicembre, Del deporte (Spanish Sports Act). The legislation explicitly recognises the right of professional sportsmen to engage in industrial action. It is regrettable that the legislation does not prescribe the procedures that must be followed in the event of an industrial action. In contrast, the Indonesian legal framework does not specifically address the right to strike in the context of sports. Consequently, there are no dedicated regulations that pertain to professional sportsmen. Consequently, the regulations pertaining to industrial actions applicable to professional sportsmen are those set forth in the Indonesian labour law, which delineates the procedural aspects of strike implementation.